2012
DOI: 10.1152/ajpendo.00296.2011
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral oxytocin suppresses food intake and causes weight loss in diet-induced obese rats

Abstract: Growing evidence suggests that oxytocin plays an important role in the regulation of energy balance and that central oxytocin administration induces weight loss in diet-induced obese (DIO) animals. To gain a better understanding of how oxytocin mediates these effects, we examined feeding and neuronal responses to oxytocin in animals rendered obese following exposure to either a high-fat (HFD) or low-fat diet (LFD). Our findings demonstrate that peripheral administration of oxytocin dose-dependently reduces foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
239
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(258 citation statements)
references
References 62 publications
17
239
1
Order By: Relevance
“…It is already well established that the hypothalamus is the regulatory center for feeding and satiety [26]. Oxytocin has also been linked to energy homeostasis mechanisms in animals, where it acts as a strong inhibitor of food intake and affects energy expenditure and glucose homeostasis [27][28][29][30][31]. Oxytocin has also been shown to play an important role in metabolism and energy balance in humans [32,33], such as reducing caloric intake with a preferential effect on fat intake [11] and reward-driven food intake in humans [34].…”
Section: Discussionmentioning
confidence: 99%
“…It is already well established that the hypothalamus is the regulatory center for feeding and satiety [26]. Oxytocin has also been linked to energy homeostasis mechanisms in animals, where it acts as a strong inhibitor of food intake and affects energy expenditure and glucose homeostasis [27][28][29][30][31]. Oxytocin has also been shown to play an important role in metabolism and energy balance in humans [32,33], such as reducing caloric intake with a preferential effect on fat intake [11] and reward-driven food intake in humans [34].…”
Section: Discussionmentioning
confidence: 99%
“…Recognizing that oxytocin inhibits weight gain in rodent models [21,41] and in humans [29], we challenged oxytocin-deficient B6;129S-Oxttm1Wsy/J mutant mice with canine source L. reuteri 2546 to determine whether this neurotropic hormone oxytocin is essential for L. reuteri 2546-induced weight control. We found that mice globally lacking oxytocin did not benefit from microbe-induced body weight Figures 5C and 5D).…”
Section: Consumption Of L Reuteri Reduces Risk For Obesity In An Oxymentioning
confidence: 99%
“…Importantly, oxytocin has also been convincingly linked with protection from obesity [17][18][19][20][21][22][23]. While the nonapeptide oxytocin is historically recognized for its role in parturition [24] and lactation [25] it has gained more recent attention for its apparent effects on prosocial behavior [26,27] and therapeutic potential in the treatment of autism spectrum disorder (ASD) [26,27], schizophrenia [26,28] and obesity [17][18][19][20][21][22][23]. A large number of ongoing investigations in humans list oxytocin as the focus in studies on caloric intake, gastric emptying, or obesity, as displayed in the ClinicalTrials.…”
Section: Introductionmentioning
confidence: 99%
“…Mice lacking oxytocin or oxytocin receptors develop late-onset obesity with little changes in daily food intake [351][352][353], and pair-feeding studies confirm that reductions in eating only partially account for oxytocin's effect on body weight, suggesting that oxytocin also controls energy expenditure [354,355].…”
Section: Oxytocinmentioning
confidence: 96%